Beneficial effects of the fructus Sophorae extract on experimentally induced osteoporosis in New Zealand white rabbits - CHAKULESKA LIDIJA; SHKONDROV ALEKSANDAR; POPOV GEORGI; ZLATEVA-PANAYOTOVA NADYA; PETROVA RENETA; ATANASOVA MARIYANA; KRASTEVA ILINA; DOYTCHINOVA IRINI; SIMEONOVA RUMYANA (Acta Pharmaceutica)
Sophora japonica is a source of several flavonol, flavone and isoflavone glycosides that are reported to positively affect menopausal symptoms including osteoporotic complications. In the present study fructus Sophorae extract (FSE) was administered orally for three months at a dose of 200 mg kg–1 in ovariectomized (OVX) New Zealand rabbits. 3D computed tomography scans and histopathological images revealed microstructural disturbances in the bones of the castrated animals. FSE recovered most of the affected parameters in bones in a manner similar to zoledronic acid (ZA) used as a positive control. The aglycones of the main active compounds of FSE, daidzin, and genistin, were docked into the alpha and beta estrogen receptors and stable complexes were found. The findings of this study provide an insight into the effects of FSE on bone tissue loss and suggest that it could be further developed as a potential candidate for the prevention of postmenopausal osteoporotic complications.